Evidence for differences in activity between socioeconomic groups at Kulubnarti, Nubia (550–800 CE), from osseous modifications of the proximal femur. (4th September 2018) - Lawrence, Austin B.; Sandberg, Paul A.; Van Gerven, Dennis P.; Sponheimer, Matt
Abstract: Past bioarchaeological analyses of human remains from the Early Christian Period site of Kulubnarti, Nubia (550–800 CE), have revealed differences in patterns of stress between two contemporaneous cemeteries (mainland [21‐R‐2] and island [21‐S‐46]) that are thought to represent separate socioeconomic groups. However, to this point, differences in activity between cemetery groups and sexes at Kulubnarti have been poorly understood. In this study, we compare patterns of two nonmetric traits (Poirier's facets and plaque) that occur on the proximal femur and have been linked to activity and femoroacetabular impingement (FAI) to better understand activity patterns at Kulubnarti. The remains of 134 adult individuals (252 femora) from two cemeteries at Kulubnarti were analyzed for the presence of Poirier's facet, plaque, and FAI. Frequencies of Poirier's facet and plaque were significantly different between cemeteries and sexes, and Poirier's facet was found only in males. Morphology consistent with FAI was significantly more common in males, and patterns of FAI morphology were different between cemeteries. Patterns in the frequencies of Poirier's facet, plaque, and FAI may indicate a difference in activity between sexes and cemeteries (socioeconomic groups), possibly related to the intensity of agricultural activity. Poirier's facet and plaque may arise via similar processes to FAI in modern athletes or may be different forms of FAI. New work should be undertaken to clarify the etiologies of Poirier's facets and plaque and to better understand their relationship to FAI.